Review of Islamic Law and Positive Law: Regarding the Obligation to Comply with the Marriage Law - Hilmi, Ismi Lathifatul; Agustar, Armi (Jurnal Syariah dan Hukum Komparatif, 2023)
This paper aims to examine the views of positive law and Islamic law on the obligation to comply with the Marriage Law. As it is known that Indonesia is a country that adheres to two laws, namely Islamic law and Positive law, then in taking a view of a provision must take into account these two aspects. This research will look at the need to obey the law under Islamic law and the positive, relevance of ijma’ to such obligations. This paper uses a normative legal approach that results in the obligation to comply with laws and regulations has been regulated in positive law, especially Article 27 paragraph (1) of the 1945 Constitution, and is also regulated in the Qur'an QS. An- Nisa verses 59 and 83, which are law-abiding as well as obeying ulil amri because state laws are formed by ulil amri and are the solution of the problems of the people using the approach of the text of revelation and publication, then it is ijma’ which is in accordance with the concept of ushul and the decision must be obeyed.